Expression and roles of Ca(v)1.3 (alpha(1D)) L-Type Ca2+ Channel in atrioventricular node automaticity - Zhang, Qian; Timofeyev, Valeriy; Qiu, Hong; Lu, Ling; Li, Ning; Singapuri, Anil; Torado, Cyril L.; Shin, Hee-Sup; Chiamvimonvat, Nipavan (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2011)
Atrioventricular node (AV node) is the hub where electrical input from the atria is propagated and conveyed to the ventricles. Despite its strategic position and role in governing impulse conduction between atria and ventricles, there is paucity of data regarding the contribution of specific ion channels to the function of the AV node. Here, we examined the roles of Ca(v)1.3 L-type Ca2+ channel in AV node by taking advantage of a mouse model with null mutation of Ca(v)1.3 (Ca(v)1.3(-/-)). Ca(v)1.3 null mutant mice show evidence of AV node dysfunction with AV block, suggesting the tissue-specific function of the Ca(v)1.3 channel. In keeping with this assertion, we demonstrate that Ca(v)1.3 isoform is highly expressed in the isolated AV node cells. Furthermore, AV node isolated from Ca(v)1.3 null mutant mice show a significant decrease in the firing frequency of spontaneous action potentials suggesting that Ca(v)1.3 L-type Ca2+ channel plays significant roles in the automaticity of the AV node. Because of the distinct voltage-dependence of Ca(v)1.2 and Ca(v)1.3 Ca2+ channels, Ca(v)1.2 alone does not suffice to maintain normal AV node function. Ca(v)1.3 currents activate at more hyperpolarizing voltage compared to Ca(v)1.2 currents. Consequently, Ca(v)1.2 Ca2+ channel cannot functionally substitute for Ca(v)1.3 isoform in the AV node of Ca(v)1.3 null mutant mice. Thus, our study demonstrates that the distinct biophysical properties of Ca(v)1.3 Ca2+ channel play critical roles in the firing frequency of AV node tissues. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: CA2+-ACTIVATED K+ CHANNEL; ADULT-RABBIT HEART; NULL MUTANT MICE; CALCIUM-CHANNELS; PACEMAKER ACTIVITY; FUNCTIONAL ROLES; SINOATRIAL NODE; CONDUCTION SYSTEM; ELECTROPHYSIOLOGICAL PROPERTIES; SYNAPTIC-TRANSMISSION